2016
DOI: 10.1017/s1049023x16000832
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Health Outcomes Among Disaster and Humanitarian Responders

Abstract: The prevalence of mental health disorders in responders may vary more and be higher than previously suggested. Overall health outcomes of responders are likely poorly monitored and under-reported. Improved surveillance systems and risk mitigation strategies should be employed in all disaster and conflict responses to better protect individual responders. Garbern SC , Ebbeling LG , Bartels SA . A systematic review of health outcomes among disaster and humanitarian responders. Prehosp Disaster Med. 2016;31(6):63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Injuries include falls, lacerations (notably chainsaw injuries), puncture wounds, abrasions, fractures, electrocutions, and motorized equipment injuries. 5,30,[47][48][49] Morbidity: Heat-Related Injury…”
Section: Mortalitymentioning
confidence: 99%
“…Injuries include falls, lacerations (notably chainsaw injuries), puncture wounds, abrasions, fractures, electrocutions, and motorized equipment injuries. 5,30,[47][48][49] Morbidity: Heat-Related Injury…”
Section: Mortalitymentioning
confidence: 99%
“…Earlier studies on relief workers generally found them to be at higher risk of developing trauma-related illness, and the level of risk depends on the intensity and duration of exposure to traumatic situations (Holloway and Everly 2009;Norris et al 2002). However, a recent systematic review of health outcomes among relief workers found a wide range of prevalence of PTSD upon returning from missions, from 0 to 36% (Garbern, Ebbeling, and Bartels 2016).…”
Section: Background On Military Deployments and Mental Healthmentioning
confidence: 99%
“…Also, local residents can enjoy a long-term good living environment (Vo, Forder, Tavener et al, 2015), and employment from tourism is promoted (Byles et al, 2014), which positively affects their mental health. However, those who have a high yearning for economic development (Garbern, Ebbeling, & Bartels, 2016), prefer to enjoy modern life, and maintain their original life and do not want their own lives interfered by the tourism industry will be resistant to this (Nukui, Midorikawa, Murakami et al, 2018). Therefore, this paper attempts to study the mental health status and influencing factors of the local people in nature reserves using the questionnaires and Kessler Psychological Distress Scale (K10).…”
Section: Introductionmentioning
confidence: 99%